Complement Profile, Ana Test, And Anti-Dsdna in Systemic Lupus Erythematosus (Sle) Patients Treated At Dr. Soetomo General Hospital Surabaya 2022–2023 - Reisya Fadhilah Noor Hafizhah; Yuliasih Yuliasih; Betty Agustina Tambunan; Lita Diah Rahmawati (Universitas Pahlawan Tuanku Tambusai, 2026)
The complement system is an important part of the innate immune system, consisting of several proteins that play a role in defending the body against infection, tissue repair, and immune complex clearance. Components C3 and C4 are major parts of this system that can describe immune response activity in autoimmune diseases such as systemic lupus erythematosus (SLE). This study aims to determine the complement levels (C3 and C4), ANA test results, and anti-dsDNA levels in patients with systemic lupus erythematosus (SLE) treated at the Dr. Soetomo General Hospital in Surabaya during the period 2022–2023. This study used a retrospective descriptive design with secondary data from the medical records of SLE patients treated at Dr. Soetomo General Hospital in Surabaya. The variables analyzed included patient characteristics (age, gender, occupation), C3 and C4 complement levels, ANA test results, and anti-dsDNA levels. The results showed that out of 1,978 SLE patient data, 274 patients met the inclusion criteria for the study. Most patients were female (81%) with the highest age range being 15–19 years (28.1%). Complement level tests showed that 57.6% of patients had below-normal C3 levels, while 51.1% of patients had normal C4 levels. Positive ANA test results were found in 52.6% of patients, while 26.6% of patients showed positive anti-dsDNA levels. Spearman's correlation analysis showed a significant negative correlation between anti-dsDNA levels and C3 levels (r = –0.498; p < 0.001) and C4 levels (r = –0.561; p < 0.001), meaning that an increase in anti-dsDNA levels was followed by a decrease in complement levels. The majority of SLE patients at Dr. Soetomo General Hospital in Surabaya were women of childbearing age. Most patients showed decreased complement levels and increased anti-dsDNA levels, which correlated with disease activity.